Effectiveness of dysphagia training for adult learning disabilities support workers. (7th April 2013) - Tredinnick, Gerlind; Cocks, Naomi
<x xml:space="preserve">Abstract</x> Accessible summary It is important to notice problems with eating, drinking and swallowing in people with a learning disability. People who have problems with eating, drinking and swallowing need support from staff to help them stay healthy. This study shows that training gives staff a better understanding and more confidence when identifying problems and supporting a person with eating, drinking and swallowing difficulties. Summary This study investigated the effectiveness of a 1‐day dysphagia training package delivered to support workers who work with adults with a learning disability. Thirty‐eight support staff took part in this study. Twenty‐five support staff received training, and 13 did not receive training and therefore acted as a control group. Three questionnaires were completed by each participant: immediately before, immediately after and a month after the training delivery. Questionnaires measured both confidence and knowledge. Findings indicated that there was a significant increase in knowledge and confidence scores in the trained group. These increases were largely maintained over a 1‐month period. There was no significant change in confidence or knowledge scores in the untrained group.